Artificial Intelligence and Law: Theoretical and Legal Features - Tereshchenko, Elena; Ivanchenko, Elena; Meleshkin, Valeriy; Zhuzhgov, Igor; Erokhina, Maria (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
Artificial Intelligence (AI) has become one of the most transformative technological phenomena in the modern digital era. This article raises fundamental theoretical and legal issues related to the classification and regulation of artificial intelligence. This study aims to examine in depth the concept, characteristics, legal nature, scope of application, and regulatory framework of artificial intelligence from an information law perspective. This study uses a qualitative method with a literature approach and a legal approach (normative juridical), where data is obtained through a literature review of various scientific literature, laws and regulations, legal documents, and relevant academic articles. In this study, the author explores various approaches in defining the concept of AI, as well as examining its legal regulations in various jurisdictions. One important finding shows that artificial intelligence law can be categorized as a legal institution within the information law framework. In addition, the issue of legal responsibility for AI actions is an important highlight, considering that artificial intelligence can act autonomously but does not yet have a clear legal subject. This article also describes the use of AI in various fields such as health, transportation, and finance, considering each sector's specific characteristics. While the benefits offered, such as efficiency and automation, the article also highlights the potential risks inherent, including privacy violations and algorithmic bias. Overall, this research provides conceptual and normative insights into the legal challenges and opportunities in the development and application of AI.